The Utility of Ambulatory pH Monitoring in Patients Presenting with Chronic Cough and Asthma. (2007) - AlHabib, KF; Vedal, S; Champion, P; FitzGerald, JM
Abstract : OBJECTIVE: To evaluate the prevalence of gastroesophageal reflux disease (GERD) in patients presenting with asthma and chronic cough. PATIENTS AND METHODS: The charts of 358 consecutive patients who were referred for ambulatory gastroesophageal pH monitoring to the Lung Centre in Vancouver, British Columbia, were reviewed, and the data of 108 (30%) patients with asthma and 134 (37%) patients with chronic cough were analyzed. The maintenance treatment for GERD was discontinued before patients underwent the pH monitoring study. One hundred eighteen (33%) patients were excluded. RESULTS: Reflux episodes identified reflux events as the percentage of time where the pH was less than four. For asthma patients, 70 (64.8%) had distal total reflux, 50 (46.3%) had distal upright reflux, 41 (38.3%) had distal supine reflux and 73 (67.6%) had other distal refluxes. Proximal total reflux in asthmatic patients was present in 56 (52%), proximal upright reflux in 55 (51%) and proximal supine reflux in 56 (52%) patients. For chronic cough patients, 70 (52.6%) had distal total reflux, 59 (44.4%) had distal upright reflux, 45 (34.4%) had distal supine reflux and 75 (56%) patients had other distal refluxes. In chronic cough patients, proximal total reflux was present in 70 (52%), proximal upright reflux in 80 (60%) and proximal supine reflux in 59 (44%). Presenting respiratory and/or reflux symptoms were absent in approximately 25% of patients with asthma and reflux, and in approximately 50% of patients with chronic cough and reflux. During pH monitoring, symptoms did not differ significantly between those with and without distal reflux in both study groups, except for more significant heartburn in patients with chronic cough and reflux (RR 2.0). CONCLUSIONS: The data of the present study support the observation that there is a high prevalence of GERD in patients with asthma or chronic cough. The use of different pH parameters for detecting acid reflux during 24 h ambulatory pH monitoring, such as proximal esophageal acid measurement, should be considered as part of the routine interpretation of such testing. A low threshold for diagnosing GERD in patients with asthma or chronic cough is essential, because respiratory and/or reflux symptoms can be absent or atypical in some of these patients.